DENGAN MENGGUNAKAN METODE AHP (ANALYTICAL HIREARCHY PROCESS) MENENTUKAN OBAT SARIAWAN YANG PALING BANYAK DIMINATI MASYARAKAT - Leon Deon; Poningsih Poningsih; Jalaluddin Jalaluddin (STMIK Budi Darma, 2019)
Many hot medicine products are marketed to the public. Because many products are marketed, making people confused in choosing the best hot medicine in the best. Hot medicine in the most popular community means that the drug is the best medicine for the community. In this research, there are two main problems in the research that can be formulated, namely whether the use of the AHP method can make the decision to determine the heat medication in the most popular community and how to look for a hot medicine decision in the most popular community. Analytic Hierarchy Process (AHP) method is used to find the ratio scale, both from discrete and continuous pair comparisons. AHP decomposes complex multi-factor or multi-criteria problems into a hierarchy. Hierarchy is defined as a representation of a complex problem in a multi-level structure where the first level is the goal, followed by the level of factors, criteria, sub-criteria, and so on down to the last level of alternatives.Keywords: Decision Support System, Analytic Hierarchy Process Method, Internal Medicine